2015
DOI: 10.11648/j.ajhr.20150305.17
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to HIV/AIDS Treatment in Nigeria

Abstract: Background: With the exception of South Africa and India, the number people living with Human Immunodeficiency Virus (PLWHA) in Nigeria exceeds that of any other country in the World. Access to HIV/AIDS treatment services remains a challenge as only 6% of PLWHAs have accessed the services. This stands in the way of achieving the National HIV/AIDS policy as well as the global goal of placing 15 million PLWHAs on treatment and care by the end of the year 2015. In order to achieve these goals, there is need to kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
2
8
1
Order By: Relevance
“…Efforts by donors have increased the roll-out of antiretrovirals to various treatment facilities, thereby seeing an increase in national viral suppression rates to 42.3% across the country, yet gaps in knowledge, service delivery, and transportation continue to dissuade people living with HIV from accessing antiretroviral treatment 35 . ART continues the HIV response by including care and support to ensure proper treatment adherence.…”
Section: Evaluation Of the Effectiveness Of Control Measuresmentioning
confidence: 99%
“…Efforts by donors have increased the roll-out of antiretrovirals to various treatment facilities, thereby seeing an increase in national viral suppression rates to 42.3% across the country, yet gaps in knowledge, service delivery, and transportation continue to dissuade people living with HIV from accessing antiretroviral treatment 35 . ART continues the HIV response by including care and support to ensure proper treatment adherence.…”
Section: Evaluation Of the Effectiveness Of Control Measuresmentioning
confidence: 99%
“…These patients face discrimination, stigma, and low acceptance in their respective communities (21,22). In these parts of the world, HIV containment is hampered by inadequate health infrastructure (23). In Sub-Saharan Africa, public discussion of sex-related issues limits the dissemination of HIV information, particularly from teachers to their students.…”
Section: Review Of Related Literature On Hiv Prevalence In Subsaharan...mentioning
confidence: 99%
“…Various studies have identified and characterized a range of barriers to accessing HIV/AIDS treatment services for PLHIV in Nigeria, including KP [ 10 - 13 ]. Abubakar Saleh categorized these barriers to ART treatment into three main groups: health system-related, patient-related, and community-related barriers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have identified and characterized a range of barriers to accessing HIV/AIDS treatment services for PLHIV in Nigeria, including KP [ 10 - 13 ]. Abubakar Saleh categorized these barriers to ART treatment into three main groups: health system-related, patient-related, and community-related barriers [ 13 ]. Health system-related barriers include poor treatment literacy, long waiting times, inadequate health infrastructure, limited availability of ART medications, and the facility not implementing person-centred or integrated approach [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%